2010
DOI: 10.3109/15622975.2010.488273
|View full text |Cite
|
Sign up to set email alerts
|

The safety and tolerability of clozapine in aged patients: A retrospective clinical file review

Abstract: Clozapine was prescribed to 75 patients (mean age 74.2 years, range 65-89) with doses ranging from 25-800 mg daily (mean 296 mg). Treatment was stopped within the review period in 37 (49%) cases. Reasons for discontinuation included death (n=14), non-fatal adverse events (n=12), patient choice (n=8) and other factors (n=3). While none of the 14 deaths could be linked directly to treatment, orthostatic hypotension might have contributed to a single fatal cerebrovascular accident. There were three cases of "red … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 16 publications
3
10
0
Order By: Relevance
“…It is reassuring that our results, like others (O'Connor et al, 2010;Snowdon and Halliday, 2011), do not suggest an increased risk of agranulocytosis or death; moreover, decreased counts are reversible with clozapine discontinuation. This line of investigation is in its earliest stages, and differences in reported risk between studies call for larger, prospective trials that more precisely delineate this, in addition to taking us beyond liability to questions relevant to treatment and clinical decision-making.…”
Section: Discussionsupporting
confidence: 57%
“…It is reassuring that our results, like others (O'Connor et al, 2010;Snowdon and Halliday, 2011), do not suggest an increased risk of agranulocytosis or death; moreover, decreased counts are reversible with clozapine discontinuation. This line of investigation is in its earliest stages, and differences in reported risk between studies call for larger, prospective trials that more precisely delineate this, in addition to taking us beyond liability to questions relevant to treatment and clinical decision-making.…”
Section: Discussionsupporting
confidence: 57%
“…It means mild residual psychotic symptoms (CGI-S=3) or moderate residual psychotic symptoms (CGI-S=4). Such improvement of psychotic symptoms thanks to clozapine was observed in different studies [15][16][17][18]. No clinically evident changes in white blood cells count in treated seniors were observed, this result can´t be compared to similar finding in literature (research for myelotoxicity of clozapine in elderly hasn´t been done).…”
Section: Discussionmentioning
confidence: 49%
“…Twenty-four studies consisting of 256,635 subjects (mean per sample = 10,693, SD = 38,419) reported on clozapine-associated myocarditis (Table 1) (Amodeo et al, 2016; Baptista et al, 2016; Butcher et al, 2015; Curto et al, 2015; Degner et al, 2000; Fernandez et al, 2004; Haas et al, 2007; Hägg et al, 2001; Hollingworth et al, 2018; Hyde et al, 2015; Ifteni et al, 2014; Joy et al, 2017; Khan et al, 2017; Kilian et al, 1999; Kishi et al, 2013; La Grenade et al, 2001; Murch et al, 2013; Nielsen et al, 2012; O’Connor et al, 2010; Poyraz et al, 2016; Reinders et al, 2004; Rohde et al, 2018; Tirupati, 2006; Youssef et al, 2016). Median follow-up was 24 months (interquartile range = 1–72 months).…”
Section: Resultsmentioning
confidence: 99%